2016
DOI: 10.1007/s11094-016-1349-6
|View full text |Cite
|
Sign up to set email alerts
|

Complexes of Glucosamine Hydrochloride and Phytic Acid in Aqueous Medium and Their Antioxidant Properties in Human Blood Plasma

Abstract: The reaction in aqueous medium of phytic acid (myo-inositol hexakisphosphate) and glucosamine hydrochloride (2-amino-2-deoxy-b-D-glucopyranose hydrochloride) formed phytic acid-glucosamine complexes of formula InsP 6 × 5GA. Their compositions were proved by elemental analysis for C, H, N, and P. IR, PMR, 13 C NMR, and 31 P NMR spectroscopy and potentiometric titration showed that the complexes of phytic acid and glucosamine were formed by H-bonds and electrostatic salt interactions. High antioxidant activity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
(19 reference statements)
0
0
0
Order By: Relevance
“…It is endogenous biosynthesis in animals and humans by glucosamination. GAH has been shown to have a variety of biological functions, including anti-inflammatory, antioxidant, and anti-tumor activities [2][3][4]. Our previous work has demonstrated that Agaricus bisporus-derived GAH regulates the bone morphogenetic protein (BMP) signaling pathway to repair skeletal damage in zebrafish [5].…”
Section: Introductionmentioning
confidence: 99%
“…It is endogenous biosynthesis in animals and humans by glucosamination. GAH has been shown to have a variety of biological functions, including anti-inflammatory, antioxidant, and anti-tumor activities [2][3][4]. Our previous work has demonstrated that Agaricus bisporus-derived GAH regulates the bone morphogenetic protein (BMP) signaling pathway to repair skeletal damage in zebrafish [5].…”
Section: Introductionmentioning
confidence: 99%